P082 The CCR9/CCL25 axis is specific to the ileum and is correlated with stricturing disease. (30th January 2023) - Gehrmann, U; Csomor, E; Monkley, S; Georgi, B; Tian, S; Cairns, J; Angermann, B; Khan, E; Nys, J; Marks, D
Abstract: Background: Crohn's Disease (CD) is a chronic disease in which inflammation is sustained by continuous influx of inflammatory leukocytes into gut mucosa and may affect all segments of the gastrointestinal tract. Immune cell trafficking is regulated via chemokine gradients and adhesion molecules such as integrins. Here we explored the expression profile of gut-specific integrin and chemokine axes in different regions of the gut to identify possible targets for treating CD patients with different disease location or phenotype. Methods: This study used transcriptomic data from gut tissue biopsies of the large and small intestine of 611 CD and 315 UC patients enrolled in a multicentred longitudinal Study of a Prospective Adult Research Cohort with IBD (SPARC IBD) obtained from the IBD Plexus program of the Crohn's and Colitis Foundation. We mapped the expression of selected chemokine receptors and their ligands as well as gut-specific integrins onto the different segments of the intestine. Expression data were then linked to available clinical disease phenotypes, as well as genotype information. Results: In both CD and UC patients, ITGA4 and ITGB7, the targets for Vedolizumab, and their endothelial ligand MADCAM1 were ubiquitously present in all regions of the gut. GPR15 and its ligand C10orf99 were predominantly expressed in colonic biopsies. On the contrary, expression of CCR9 and its ligand CCL25 were specific to the terminal ileum with only minimal transcriptional activity in the colon. Expression of CCL25 was significantly increased in patients with penetrating and/or stricturing CD, a disease feature associated with ileal CD that has high impact for patients and is currently an unmet for IBD patients. Further, we identified an expression quantitative trait loci (eQTL) upstream of the CCL25 promoter linked to small bowel expression of CCL25. Conclusion: Our data highlight the potential for targeting the CCR9/CCL25 axis as a treatment for small bowel Crohn's Disease which may have been incompletely targeted to date by small molecule inhibitors. Further investigations are warranted to identify a mechanistic link between this pathway and penetrating and stricturing disease.